One-Step Synthesis of Porous Graphitic Carbon Nitride and the Photocatalytic Performance under Visible-Light Irradiation - Zhang, Ligang; Zhang, Naipeng; Zhang, Dejin; Ouyang, Wenzhu; Xie, Yong (Journal of Research Updates in Polymer Science, 2023)
Porous graphitic carbon nitride (pg-C3N4) was synthesized via a facile one-step dicyandiamide (DCDA) high-temperature calcination method using heat-labile ammonium bicarbonate (NH4HCO3) as the gaseous template, and different pg-C3N4 materials were obtained by mixing various mass ratios of NH4HCO3 into DCDA. The micro-structures and -morphologies of the porous materials were characterized by X-ray diffraction (XRD) and Scanning Electron Microscope (SEM) respectively, and the photocatalytic degradation of methylene blue (MB) dye was tested under visible-light irradiation. It is found that the thermal decomposition of NH4HCO3 promoted destruction of the layer-structured g-C3N4 and increment of the specific surface area, producing more porous structures on the material surfaces, which is considered to be vital for the improvement of photocatalytic performance. Compared with the photocatalyst calcined by pure DCDA, the pg-C3N4 photocatalysts obtained by mixing the two raw materials performed better on MB dye degradation. Moreover, photocatalytic efficiency of the catalysts improved significantly with increasing NH4HCO3 contents in the raw materials. The degradation rate photocatalyzed by pg-C3N4 materials can reach more than 90% within 1.5 h, 6.5 times higher than that of the control material. It comes up to 99% at 2 h, basically achieving the complete degradation and decolorization of MB dye.